STUDENTS’ DIFFICULTIES IN WRITING PROCEDURAL TEXT AT THE ELEVENTH GRADE STUDENTS OF SMA N 1 O’O’U - Zai, Immannuel (Universitas Nias Raya, 2023)
This research aimed to analyze the students’ difficulties in writing procedural text. This research is designed in qualitative research with descriptive approach. The data of this research are students’ worksheets about writing procedural text and interview result. The procedures used during analyzing the data were reading/memoing, describing, classifying. Based on the data analysis, it was found that there were difficulties faced by eleventh grade students of SMA N 1 O’O’U. First, in writing generic structures of procedural text which lie on writing material or ingredients, step and tips. The second, in writing language features of procedural text which lies on writing noun phrase pattern and using temporal conjunction. The factors caused students difficulties in writing procedural text are the lack of vocabulary, motivation and student’s lack of grammar understanding. It is suggested to the English teacher to teach students intensively on generic structure and language features of procedural text, the students to learn more about generic structure and language features of procedural text. Also readers to use this research as a guidance in conducting the relevant research to sharpen and enlarge their knowledge about students difficulties in writing procedural text.